Jika f-¹(x) merupakan invers dari fungsi f(x) dengan f(2x)=4x-8/10x+6 dan x#-3/5, rumus fungsi f-¹(x) adalah
Jawaban Terkonfirmasi
Jawab:
fungsi invers
komposisi fungsi
Penjelasan dengan langkah-langkah:
f(2x) = (4x – 8) / (10 x + 6)
f(2x) = y
2x= y
x= 1/2 y
f(y) = { 4*1/2 y – 8 }/ {10 .1/2 y + 6 }
f(y) = { 2y – 8 } / { 5y + 6 }
f(x) = (2x – 8) / (5x + 6)
.
f(x) = (ax + b) / (cx + d)
f⁻¹ (x) = ( – dx + b ) / (cx – a )
.
f(x) = (2x – 8) / (5x + 6)
f⁻¹ (x) = (-6x -8) / (5x – 2)
f⁻¹ (x) = (6x + 8) / (2 – 5x) dengan x≠ 2/5